The postwar development of Japanese studies in the United States - Hardacre, Helen, 1949- (Leiden ; Boston : Brill, 1966)
The present volume documents the postwar history of United States scholarship on Japan. A careful selection of North American scholars under the general editorship of Helen Hardacre shows that a range of factors have directed Japanese studies in the United States since 1945. Among these factors are social and political change in Japan and the United States, shifts in dominant scholarly concerns about Japan, and changing evaluations of area studies. The general aim of the volume is to put current debates in historical perspective and to help assessing the field's achievements. It identifies areas requiring more work and charts directions for the future.
Introduction / Helen Hardacre -- Sizing Up (and Breaking Down) Japan / John W. Dower -- The Study of Japan's Early History / Martin Collcutt -- Tokugawa Japan: The Return of the Other? / Harold Bolitho -- The Meiji Restoration: a Historiographical Overview / Albert M. Craig -- American Studies of Japanese Foreign Relations / Akira Iriye -- Japanese Art Studies in America since 1945 / John M. Rosenfield -- The Postwar Development of Studies of Japanese Religions / Helen Hardacre -- "The Way of the World": Japanese Literary Studies in the Postwar United States / Norma Field -- When and Where Japan Enters: American Anthropology since 1945 / Jennifer Robertson -- The Turbulent Path to Social Science: Japanese Political Analysis in the 1990s / Kent E. Calder -- The Development of Japanese Legal Studies in American Law Schools / Frank K. Upham -- Taking Japanese Studies Seriously / Andrew Gordon.
Includes bibliographical references and index.
Keywords: Japan -- Study and teaching -- United States